Implementation of Public Policy for Street Vendors Arrangements in Bandung City - Muksin, Isra (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This research delves into the complex issues surrounding the implementation of public policy aimed at organizing street vendors in Bandung City. The presence of street vendors has become intertwined with concerns related to public order and security, frequently culminating in conflicts between these vendors and government authorities seeking to regulate their presence in prohibited public areas. Motivated to resolve disputes without violence, the Bandung City Government has called for immediate measures to manage street vendors effectively. This study seeks to understand the factors hindering the effective implementation of the policy on street vendor arrangement, exploring whether the policy execution aligns with the planned actions and its subsequent impact on both individuals and groups within society. Utilizing qualitative research methods, including observation, in-depth interviews, and document studies, this research engages key informants such as executing officials, beneficiaries, affected groups, and relevant stakeholders involved in the Local Regulation on Structuring of Street Vendors in Bandung City. Employing the implementation theory and model from Grindle (2017), examining policy implementation considers the nuances contributing to its ineffectiveness. The findings reveal many challenges, including conflicting interests, ongoing debate on policy benefits, overlapping goals, limited decision-making authority, inadequate resources, and contextual conflicts between governmental and non-governmental entities. The study concludes that a comprehensive strategy is required to address these challenges and foster stakeholder collaboration to enhance the policy's effectiveness.